GE_GERICHTE C/13354/2009 vom 15. April 2011 - GE Cour de justice (2011)
; BANQUE ; RESPONSABILITÉ DE DROIT PRIVÉ ; DILIGENCE ; BANQUE RESTANTE ; MONNAIE(UNITÉ MONÉTAIRE) | CPC. 405.1. CO. 100. CO. 97. CO. 84.2